Analisis Penyusunan Laporan Keuangan Cabang UMKM X Berdasarkan SAK EMKM - Purba, Dea Natalia; Simanjuntak, Putri Christina; Khoirunnisa, Salsabila; Putri, Popi Andika; Permata, Irma Dwi (Asosiasi Dosen Akuntansi Indonesia, 2023)
This study aims to analyze the Financial Report of UMKM X Branch Based on SAK EMKM. Financial reports are the result of the accounting process used to communicate financial data and business activities to stakeholders. There are various types of financial reports depending on the intent and purpose. This financial report has its important concerning the company's financial condition in general. In practice, financial reports must be prepared based on the applicable SAK. Analysis of factors that influence the perception of UMKM entrepreneurs regarding the importance of financial reports based on SAK EMKM needs to be carried out. These factors include the level of education of SAK EMKM, use of information technology, length of service, sales, and provision of information, and the ability to socialize